Recognition Across French-German Divides: The Social Fabric of Freedom in French Theory. Issue 1 (2nd January 2021) - Honneth, Axel; Bankovsky, Miriam
ABSTRACT: In his recent book, Recognition: A Chapter in the History of European ideas (2021), Honneth has explained how he understands the French concept of recognition. This article places Honneth's latest interpretation in the context of his long-standing and evolving engagement with French theory over several decades. Honneth acknowledges his significant debt to a French tendency to view recognition as a problem for self-realisation (and not an opportunity). Bourdieu's and Boltanski's account of how ambitions become limited by the availability of capital and the internalisation of class was a major breakthrough in Honneth's intellectual development. Other formative French influences included the articulation of denigration in existentialist phenomenology, and the idea of regulative power in Foucault, with "deconstructive" asymmetrical care presented as productive but comparatively less important. The discussion also reveals why Honneth presents the "German" concept of recognition as having basic explanatory force (as an opportunity for self-realisation), and why he resists what he views as a French-influenced tendency (also present in some contemporary German critical theory) to depict recognition as ambivalent. The discussion reveals, on one hand, how working across perceived divides can be immensely productive, and, on the other hand, why a French-German divide remains entrenched in contemporary thinking.